2021
DOI: 10.3390/ijerph18147388
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Health Literacy and Neighbourhood Features: HBSC Findings from Czech Republic, Poland, and Slovakia

Abstract: The role of supportive environments on health, wellbeing, and longevity has been widely recognized. However, there is no strong empirical evidence on the association between health literacy (HL) as a particular health-related competence and neighbourhoods. Therefore, the aim of the study was to assess the association between the features of neighbourhoods and the level of HL competencies of young people from three countries (Czech Republic, Poland, Slovakia). Self-reported data from an international sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The strong positive correlation between HL and both family affluence and the social and structural aspects of the environment in which school-aged children grow up was confirmed by the authors of this article in previous studies [ 21 ] that covered 11,521 students aged 13–15 in three Central and Eastern European countries (Slovakia, Czech Republic and Poland). This correlation was also shown in Lithuanian research, in which it was demonstrated that the factor with the greatest impact on raising HL levels in young people is school [ 22 ].…”
Section: Introductionsupporting
confidence: 80%
“…The strong positive correlation between HL and both family affluence and the social and structural aspects of the environment in which school-aged children grow up was confirmed by the authors of this article in previous studies [ 21 ] that covered 11,521 students aged 13–15 in three Central and Eastern European countries (Slovakia, Czech Republic and Poland). This correlation was also shown in Lithuanian research, in which it was demonstrated that the factor with the greatest impact on raising HL levels in young people is school [ 22 ].…”
Section: Introductionsupporting
confidence: 80%
“…Clearly, HC is a complex research issue that is deeply connected to a variety of different disciplines. In addition, the analysis of previous studies illustrated that HC research worldwide has focused on several themes, mainly including the doctor–patient relationship [ 12 ], HIV prevention and control [ 15 , 16 ], media interferences [ 13 , 14 ], the effect of HC [ 17 ], the environment of HC [ 18 ], health promotion, health education and health literacy [ 19 , 20 , 21 ], and special topics (e.g., euthanasia [ 22 ] and homosexuality [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…A notable finding was the nearly twofold increase in the Intraclass Correlation Coefficient (ICC) during the study periods, highlighting the extent to which the HLSAC-5 index variability depended on school-specific characteristics. Earlier studies employing the ICC noted more significant diversity in Polish schools compared to those in the Czech Republic and Slovakia, both in terms of health literacy (HL) levels and family wealth [35]. This suggests that it may be a distinctive feature of Poland that variations that in social backgrounds at the school level are more pronounced.…”
Section: Determinants Of Hl Index and Its Changementioning
confidence: 99%